Peran Motivasi Belajar, Self-Efficacy, dan Dukungan Sosial Keluarga Terhadap Self-Regulated Learning pada Siswa - Ecep Mulyana; Mujidin Mujidin; Khoirudin Bashori (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
The purpose of this research is to know the role of learning motivation, self-efficacy and family support in self-regulated learning of the 11th grade of SMA N 2 Bantulâ€™s Students. There were as many as 248 students in the population of the 11th grade of SMA Negeri 2 Bantul and 72 of them were selected as samples using cluster random sampling technique. The data were collected by using learning motivation scale, self-efficacy, family support and self-regulated learning. The data analysis technique made use of multiple regression analysis and partial correlation technique. The regression analysis indicated positive correlation between learning motivation, self-efficacy and family support, and self-regulated learning with F value of 37.345, p = 0.000 (p < 0.05). There was positive impact of learning motivation to Self-Regulated Learning with t = 2.767, p = 0.007 (p < 0.05). There was a positive role of Self-Efficacy to Self-Regulated Learning with t = 3.532 and p = 0.001 (p < 0.05),Â  a positive role of Family Support to Self- Regulated Learning with t = 2.267 and p = 0.027 (p < 0.05). This research can be used as a reference in the field of guidance and counseling, psychological counseling, or school psychology program within which it was mainly related to the increase in motivation, self-efficacy, social support families and self-regulated learning in learning activities of the students.